(untitled) (Polifonia, 2022)
In this paper, the relationship body, knowledge, and social practices within a decolonial perspective is addressed through a study on discourses of care and caring in the global COVID-19 syndemic by communities representing three vulnerable groups in Brazil - the Indigenous peoples, the Quilombolas, and the Landless Rural Workers Movement. These groups have been severely affected by the disease as national containment policies have failed to respond to their specific needs and disregarded their philosophies and practices of care. Our corpus comprises images, videos, and written materials produced by members of these communities and by government authorities on the matter of COVID-19. They were gathered from social media and websites under the thematic, qualitative enunciative criteria “COVID-19 + minority groups in Brazil”. A transcultural and discursive analysis of the data was performed to answer the following research questions: How have these communities resisted the necropolitics of the Brazilian government in the syndemic? How is care being discursivized by them? Our results point to a concept of care that is always collective, from which it is impossible to think of a form of human existence that could be only individual. Such concept materializes a non-Eurocentric, non-capitalist form of intelligibility on living collectively and caring, a view in which to live means to care and for a dignified existence.